SIGNIFIKANSI APOLOGETIKA TRINITARIAN CORNELIUS VAN TIL DALAM MENGHADAPI GERAKAN ZAMAN BARU - Sutjipto Subeno (Verbum Christi: Jurnal Teologi Reformed Injili, 2014)
The Challenge of the New Age Movement toward Christian Faith is becoming more difficult in early XXI Century, especially in Indonesia which based on Eastern Culture. Eastern culture, with its mystical nuance, is a very fertile field for New Age Movement. With the rapid growth of Charismatic movement, the challenge toward true Gospel is getting worse. On the other hand, Cornelius Van Til built his apologetics for defending Christian Faith from its dilutions. Apologetics is not a tool or an armor to kill others, nor to humiliate other religions or philosophies, but it is meant to bring people to know the True God and be saved. This paper tries to show the significance of Van Til?s approach on apologetics which is Trinitarian in essence toward the influence of New Age Movement in Christian society. The purpose is to let people, especially Christians, know the True Trinitarian God, instead of Eastern mystical or Pantheistic God of the New Age.?